2012
DOI: 10.1177/0363546512460637
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age on the Effectiveness of Neuromuscular Training to Reduce Anterior Cruciate Ligament Injury in Female Athletes

Abstract: Background In female athletes, sports-related injuries to the anterior cruciate ligament (ACL) increase during adolescence and peak in incidence during the mid- to late teens. Although biomechanical investigations indicate that a potential window of opportunity exists for optimal timing for the initiation of integrative neuromuscular training (NMT) in young female athletes, the influence of the timing of initiation of these programs on the efficacy of ACL injury reduction has yet to be evaluated. Hypothesis/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
296
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 284 publications
(306 citation statements)
references
References 68 publications
4
296
0
6
Order By: Relevance
“…Therefore, given the recent decline in both of these fitness parameters, any long-term strategy should prioritize the development of muscle strength and motor skill proficiency during the primary school years. It is imperative that youth engage in training modalities to develop muscular strength and fundamental movement skills in early childhood to maximize their modifiable neuromuscular systems (28,92). These evidence-based guidelines challenge previous athletic development models (8) and counter preconceived concerns surrounding structured resistance training for children.…”
Section: Problem 1: Physical Inactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, given the recent decline in both of these fitness parameters, any long-term strategy should prioritize the development of muscle strength and motor skill proficiency during the primary school years. It is imperative that youth engage in training modalities to develop muscular strength and fundamental movement skills in early childhood to maximize their modifiable neuromuscular systems (28,92). These evidence-based guidelines challenge previous athletic development models (8) and counter preconceived concerns surrounding structured resistance training for children.…”
Section: Problem 1: Physical Inactivitymentioning
confidence: 99%
“…Recently, researchers have proposed that for those athletes who have specialized in a single sport at an early age, physical training should concentrate on enhancing generic movement skills and addressing muscle weakness or imbalances ( 5 9), instead of being exposed to sport-specific performancedriven training. Providing progressive and mul-tifaceted training opportunities for such athletes to develop more fundamental movement skills may overcome the propensity for early specializing athletes to be at increased risk for a sports-related injury, illness, or burnout (45,92). It is accepted that not all acute injuries are unavoidable in sport; however, practitioners should be cognizant of risk factors that may predispose youth to overuse injuries.…”
Section: Problem 3: Early Sport Specializationmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrative neuromuscular training is ideally initiated in early adolescents with the most profound effects occurring at younger ages (41,42). Training pre-PHV should aim to improve neuromuscular strength, fundamental movement skills, and speed (30).…”
Section: Long-term Athlete Developmentmentioning
confidence: 99%
“…ACL injury prevention using neuromuscular training is highly successful in the adolescent population [48]. Swart et al [62] also concluded these programmes are cost-effective.…”
Section: Clinical Relevant Summarymentioning
confidence: 99%